Pemetaan Batimetri dan Karakteristik Morfologi Dasar di Sungai Manggar Sekitar Jembatan Dua Manggar Kecamatan Balikpapan Timur Kota Balikpapan sebagai Indikasi Potensi Gerusan Lokal - Muhammad Fajar Dharu Kusuma; Radik Khairil Insanu; Feri Fadlin; Nia Kurniadin (Geomatics Technology Study Program, Politeknik Pertanian Negeri Samarinda, 2026)
Manggar River is part of the Manggar Kecil watershed in Balikpapan City, covering an area of 24.07 km² and emptying into the Makassar Strait. The river is actively traversed by various types of watercraft near Jembatan Dua Manggar (Manggar Second Bridge), yet no bathymetric data have been available to support navigational safety, and no prior study has examined the riverbed morphology or potential local scour around this bridge. This study aimed to map the underwater topography of the Manggar River around Jembatan Dua Manggar through hydrographic survey, to interpret its morphological characteristics, and to identify potential scour or sedimentation zones that may affect navigational safety and infrastructure. Data collection was conducted on 8–9 March 2024, comprising bathymetric sounding using a Map Sounder at 5-second intervals, 25-hour tidal observation, and riparian topographic measurement using a Comnav T300 geodetic GPS. Survey lines were planned in cross and longitudinal patterns with 30-meter intervals. Depth data were corrected against the Mean Sea Level (MSL) value of 1.320 m derived from tidal observations. Processing yielded 1,036 depth points, ranging from a shallowest depth of -1.1616 m at the downstream section to a deepest of -15.442 m upstream, with an average correction difference of 1.15 m. River bed topography varies from gentle slopes in the downstream reach (average 2–3 m) to a scour-hole (trough) formation upstream reaching a maximum depth of 15.442 m approximately 80 m from the bridge, indicating a potential local-scour zone that warrants periodic monitoring. A bathymetric map with 1-m minor and 5-m major contour intervals was produced using AutoCAD Civil 3D and ArcGIS 10.8 software, and can serve as baseline data for future monitoring of riverbed morphology changes and local-scour evaluation around Jembatan Dua Manggar.